(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Cicatricial Alopecia (CA) is a rare, but significant group of trichologic disorders characterized by the progressive and irreversible loss of hair follicles, leaving little hope for a return to normal hair growth patterns. However, little information exists on cicatricial alopecia study in Bangladesh. The purpose of this study was to evaluate the pattern of CA in a tertiary care teaching hospital of Bangladesh. Materials and methods: This is a descriptive cross-sectional study was carried out in the Department of Dermatology and Venereology of Chittagong Medical College Hospital (CMCH) Bangladesh, between the periods of September 2018 to December 2019. Results: Out of 77 patients, most of the patients (42.9%) were 31-40 years age group with mean ± SD age was 33.1 ± 12.1 years. There was female (59.7%) predominance in the study. Among the patients, Primary Cicatricial Alopecia (PCA) were 85.7% and secondary cicatricial alopecia were 14.3%. The most common pattern of PCA was Discoid Lupus Erythematosus (DLE) 44.1% followed by Lichen Planopilaris (LPP) 19.5%. There were 3 (3.9%) patients of Kerion and 2 (2.6%) patients each of En coup de sabre, Nevus Sebaceous (NS) and trauma among secondary CA. Most frequents symptoms were scaling (16.9%) and pruritus (14.1%). The most affected regions were the vertex (75.3%) and parietal (63.3%), with associated involvement in the skin, mucous membrane and nail. Conclusion: There was a higher frequency of CA in this study among female and middle-aged patients. Over SCA, PCA is more common.CA has always been a diagnostic and therapeutic challenges to dermatologists. Proper identification and differentiation of pattern of cicatricial alopecia is necessary for early diagnosis and to design appropriate treatment and to improve the quality of life of patient. JCMCTA 2024 ; 35 (2) : 141-145